Imaging blood vessels of the head and neck. - Sellar, R J (1995)
ATHEROSCLEROTIC DISEASE: Patients with transient ischaemic attacks or a non-disabling stroke who are surgical candidates should be screened with Doppler ultrasound, or MRA/CT, or both. The choice will depend on local expertise and availability. If DUS is used it is recommended that the equipment is regularly calibrated and a prospective audit of results, particularly of those patients that go on to angiography, is maintained locally. Those patients found to have the DUS equivalent of a 50% stenosis should have angiography only if surgical or balloon angioplasty treatment is contemplated. Angiography should be performed with meticulous technique to minimise risks. ANEURYSM AND ARTERIOVENOUS MALFORMATIONS: Angiography remains the investigation of choice for patients with subarachnoid haemorrhage. Magnetic resonance angiography and CT can demonstrate the larger aneurysm but because even small aneurysms can rupture with devastating effects, these techniques are not the examination of first choice. Angiography is also the only technique that adequately defines the neck of an aneurysm. This information is becoming increasingly important in management decisions-for instance, whether to clip or use a coil. Likewise angiography is the only technique to fully define the vascular anatomy of arteriovenous malformations although the size of the nidus can be monitored by MRA and this is a useful method of follow up after stereotactic radiosurgery, embolisation, or surgery. There are specific uses for MRA such as in patients presenting with a painful 3rd nerve palsy and as a screening test for those patients with a strong family history of aneurysms. VASCULITIS, FIBROMUSCULAR HYPERPLASIA, AND DISSECTION: These rare arterial diseases are best detected by angiography, although there are increasing reports of successful diagnosis by MRA. There are traps for the many unwary and MRA does not give an anatomical depiction of the arteries but a flow map. Slow flow may lead to signal loss and a false positive diagnosis of vasculitis.